EDUKASI TENTANG DEABETES MELLITUS DAN PEMERIKSAAN KADAR GULA DARAH DI KELURAHAN PAPPOLO - Sumarni, Sumarni; Andi Ria Metasari; Ermawati, Ermawati; Susilawati, Susilawati; Sriwidyastuti, Sriwidyastuti (Nusantara Hasana Journal, 2024)
Background : Diabetes mellitus is classified as a chronic disease caused by dysfunction of insulin to secrete insulin or resistance to insulin occurs so that the body cannot use the insulin produced effectively. Diabetes mellitus causes hyperglycemia or increased blood glucose. High blood sugar levels are a common effect of uncontrolled diabetes mellitus and have serious damage to many body systems, especially the nerves and blood vessels. (Global, 2019). Solving method : The activity was carried out in Pappolo Village, Tanete Riattang District, Bone Regency, targeting pregnant women. The form of activity is in the form of DMG counseling using pamphlets, before and after the counseling, respondents fill out questionnaires as the results of the pretest and posttest, then blood sugar levels are measured. Results : Most of the knowledge of pregnant women before being given counseling was quite good, there was an increase in knowledge after the counseling activities were carried out. The results of measuring blood sugar levels for most pregnant women are still within the normal range. Pregnant women's blood sugar levels that are more than normal require further examination. Conclusion : Counseling using pamphlets can increase respondents' knowledge of pregnant women. Most of the results of measuring blood sugar levels in pregnant women are still within normal limits.